Effect of Extremely Low Frequency Magnetic Field on the Growth Rate of Bacteria - Hassan, Akhink Akram (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2015)
Developments in technology has resulted an increase in the use of electrical appliances. Electrical appliances use an alternating current with a frequency of 50 Hz. This alternating current generates an electromagnetic field which is also varies with time. This type of electromagnetic field is classified as a low frequency magnetic field that fills our living environment. In this thesis, the effect of this low frequency magnetic field is investigated on the biological systems. Escherichia coli (prokaryote) (ATCC 25922) and Drosophila melanogaster (eukaryote) are used as two different biological systems. Escherichia coli is exposed to low frequency magnetic field for three different magnetic field intensities. It is shown that the low frequency magnetic field decreases the growth rate of the bacteria. Drosophila melanogaster is exposed to low frequency magnetic field and shown that the low frequency magnetic field affects the number of pupa generation negatively. Keywords: Extremely low frequency magnetic field, Escherichia coli (E.coli ATCC25922), drosophila melanogaster (fruit fly).

ÖZ : Teknoloji alanında yaşanan gelişmeler, elektrikle çalışan aletlerin kullanımında artışa neden olmuştur. Elektrikle çalışan aletler, 50 Hz frekansına sahip alternatif akımla çalışmaktadır. Bu alternatif akım, zamanla değişen elektomanyetik alanlar üretmektedir. Bu tip elektromanyetik alanlar düşük frekanslı elektromanyetik alan olarak sınıflandırılmakta, ve yaşadığımız çevreyi sarmalamaktadır. Bu tezde, düşük frekanslı manyetik alanların biyolojik sistemler üzerindeki etkileri incelenmiştir. Biyolojik sistem olarak prokaryot hücre yapısına sahip koli basili (Escherichia coli, ATCC 25922) ile ökoryat hücre yapısına sahip meve sineği (drosophila melanogaster) kullanılmıştır. Koli basili, düşük frekanslı üç farklı manyetik alan şiddetine maruz bırakılmıştır. Düşük frekanslı manyetik alanların koli basili bakterisinin büyüme hızına olan olumsuz etkisi gösterilmiştir. Meyve sineği de düşük frekanslı manyetik alana maruz bırakılmış ve yavrulama sayısına olan olumsuz etkisi gösterilmiştir. Anahtar Kelimeler: Düşük frekanslı manyetik alanların, Escherichia coli(E.coli ATCC 25922), Drosophila melanogaster (meyve sinegi).
Master of Science in Physics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2015. Supervisor: Prof. Dr. Özay Gürtuğ.
Keywords: Physics; Extremely Low Frequency Magnetic Fields - Health aspects; Extremely Low Frequency Magnetic Fields - Physiological effects; Electromagnetics - Magnetic fields - Physiological effect - Radiation effects; Magnetic Fields - Effects on - Biological Systems; Extremely low frequency magnetic field; Escherichia coli (E.coli ATCC25922); drosophila melanogaster (fruit fly)